Antimicrobial Prophylaxis in Robot-Assisted Laparoscopic Radical Prostatectomy: A Systematic Review - Eva Falkensammer; Ece Erenler; Truls E. Bjerklund Johansen; Lazaros Tzelves; Laila Schneidewind; Yuhong Yuan; Tommaso Cai; Bela Koves; Zafer Tandogdu (MDPI AG, 2023)
It remains unclear whether antibiotic prophylaxis (AP) should be recommended or discouraged in robot-assisted laparoscopic radical prostatectomy (RALP) for prostate cancer (PCa). The development of microbial resistance and side effects are risks of antibiotic use. This systematic review (SR) investigates the evidence base for AP in RALP. A systematic literature search was conducted until 12 January 2023, using Embase, MEDLINE, Cochrane CENTRAL, Cochrane CDSR (via Ovid) and CINAHL for studies reporting the effect of AP on postoperative infectious complications in RALP. Of 436 screened publications, 8 studies comprising 6378 RALP procedures met the inclusion criteria. There was no evidence of a difference in the rate and severity of infective complications within 30 days after RALP surgery between different AP protocols. No studies omitted AP. For patients who received AP, the overall occurrence of postoperative infectious complications varied between 0.6% and 6.6%. The reported urinary tract infection (UTI) rates varied from 0.16% (4/2500) to 8.9% (15/169). Wound infections were reported in 0.46% (4/865) to 1.12% (1/89). Sepsis/bacteraemia and hyperpyrexia were registered in 0.1% (1/1084) and 1.6% (5/317), respectively. Infected lymphoceles (iLC) rates were 0.9% (3 of 317) in a RALP cohort that included 88.6% pelvic lymph node dissections (PLND), and 3% (26 of 865) in a RALP cohort where all patients underwent PLND. Our findings underscore that AP is being administered in RALP procedures without scientifically proven evidence. Prospective studies that apply consistent and uniform criteria for measuring infectious complications and antibiotic-related side effects are needed to ensure the comparability of results and guidance on AP in RALP.